PERENCANAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MADRASAH TSANAWIYAH DARUT THALIBIN PONTEH GALIS PAMEKASAN - akhmad Mudarris; Siti Munawaroh; Suwistiyonengsih Suwistiyonengsih (Fakultas Agama Islam Universitas Islam Madura, 2023)
Learning activities are an activity that is indispensable for every individual. Because by doing this learning activity, the individual will be able to develop properly. When we talk about this learning activity, we will probably immediately set our sights on the learning activities that take place in schools. It crosses our view, how can learning activities in the school run effectively? While if the teacher want to get an effective learning activity requires many components that must be considered, including educators, students, learning media, learning materials, learning strategies and planning learning activities. One of the most important elements in a learning activity is the existence of a good learning plan. Planning basically determines the activities to be carried out in the future. This activity is intended to organize various resources so that the results achieved are as expected.